PANCASILA PERSPECTIVE MARRIAGE SYSTEM: HARMONY OF NATIONAL VALUES IN FAMILY INSTITUTIONS - Jalil, Dul; Fariduddin, Ecep Ishak; Yasir, Muhammad Farhan Qurroto (IBN KHALDUN BOGOR, 2024)
This article attempts to explain that marriage is defined as a spiritual and physical bond between a man and a woman to achieve happiness. However, in reality, many marriages are forced, resulting in unhappiness. This goes against the purpose of marriage stated in the law. The inclusion of the phrase